2017
DOI: 10.1515/zireb-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Current Account Balance and Export Performances: Evidence Based on New EU Countries

Abstract: In this paper, we investigate whether the differences in the current account balance and export performances for a new EU countries are a result of exchange rate policies. The analysis shows that countries with a flexible exchange rate have better export performances and the current account balance in the pre-crisis period. The obtained results show that movements in the current account balance are mainly driven by domestic variables. In the countries with a flexible exchange rate, real and nominal depreciatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…While in emerging Europe, rising investment has a more substantial role than declining savings, in the case of the Eurozone periphery imbalances are results of declining private sector saving. Bogdan et al (2017) examined whether the exchange rate policies affect current account balance and export performances in new member states of the European Union. The authors revealed that countries with a flexible exchange rate have better performance in current account and export.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While in emerging Europe, rising investment has a more substantial role than declining savings, in the case of the Eurozone periphery imbalances are results of declining private sector saving. Bogdan et al (2017) examined whether the exchange rate policies affect current account balance and export performances in new member states of the European Union. The authors revealed that countries with a flexible exchange rate have better performance in current account and export.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analysis of the current account balance and export efficiency in the new EU member states shows that the current account balance and export activity were more efficient in countries with floating exchange rates in the precrisis period. In addition, it was noted that the exchange rate policy could still be a useful measure in enhancing exports [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is in line with the results of research from several researchers ENTREPRENEURSHIP AND SUSTAINABILITY ISSUES ISSN 2345-0282 (online) http://jssidoi.org/jesi/ 2020 Volume 7 Number 4 (June) http://doi.org/10. 9770/jesi.2020.7.4(55) such as Wanjau (2014), and Bogdan, Cota and Erjavec (2017). They prove that the increase in the exchange rate has a negative influence on current account.…”
Section: Introductionmentioning
confidence: 98%
“…The researcher recommends the government can define an exchange rate policy that leads to increased export demand so that the current account deficit (CAD) can be reduced and ultimately economic growth can be achieved sustainably. Bogdan, Cota and Erjavec (2017) have examined the relationship between current account balance and export performances in new EU countries. This study was conducted in 2017 using a linear regression method by entering exchange rate as one of its independent variable.…”
Section: Introductionmentioning
confidence: 99%